Growth of 28Si Quantum Well Layers for Qubits by a Hybrid MBE/CVD Technique. (1st February 2023) - Liu, Yujia; Gradwohl, Kevin-Peter; Lu, Chen-HSun; Yamamoto, Yuji; Remmele, Thilo; Corley-Wiciak, Cedric; Teubner, Thomas; Richter, Carsten; Albrecht, Martin; Boeck, Torsten
Abstract : Isotopically enriched 28 Si quantum well layers in SiGe/Si/SiGe heterostructures are an excellent material platform for electron spin qubits. In this work, we report the fabrication of 28 SiGe/ 28 Si/ 28 SiGe heterostructures for qubits by a hybrid molecular beam epitaxy (MBE) / chemical vapour deposition (CVD) growth, where the thick relaxed SiGe substrates are realised by a reduced-pressure CVD and the 28 SiGe/ 28 Si/ 28 SiGe stacks are grown by MBE Here, we achieve a fully strained 28 Si quantum well layer in such heterostructures with a 29 Si concentration as low as 200 ppm within the MBE grown layers. It concludes that 29 Si primarily originates from the residual natural Si vapour in the MBE chamber. A reliable surface preparation combining ex situ wet chemical cleaning and in situ annealing and atomic hydrogen irradiation offers epitaxy ready CVD grown SiGe substrates with low carbon and oxygen impurities. Furthermore, we also present our studies about the growth temperature effect on the misfit dislocation formation in this heterostructure. It shows that the misfit dislocation formation is significantly suppressed at a low MBE growth temperature, such as 350 °C.